An outbreak of multidrug-resistant Pseudomonas aeruginosa in a burns service in the North of England: challenges of infection prevention and control in a complex setting. Issue 4 (December 2018) - Decraene, V.; Ghebrehewet, S.; Dardamissis, E.; Huyton, R.; Mortimer, K.; Wilkinson, D.; Shokrollahi, K.; Singleton, S.; Patel, B.; Turton, J.; Hoffman, P.; Puleston, R.
Summary: Background: Burns patients are at high risk of nosocomial infection, and Pseudomonas aeruginosa is one of the most common causes of wound and systemic infections resulting in significant morbidity and mortality in burns patients. Aim: To describe an outbreak of multidrug-resistant P. aeruginosa (MDR-Pa) at a specialist burns service and highlight the challenges in identifying the reservoir of infection despite extensive epidemiological, microbiological, and environmental investigations. Methods: Multi-disciplinary outbreak control investigation. Findings: Following an inter-hospital transfer of a burns patient from another country, an admission screen revealed that the patient was colonized with MDR-Pa. Subsequently nine more patients contracted MDR-Pa in the period from November 2015 to September 2017. Given the relatively long gap between confirmation of the index and subsequent cases, it was not possible to identify with certainty the reservoirs and mechanisms of spread of infection, although contamination of the burns service environment and equipment are likely to be contributory factors. Conclusion: Preventing infection transmission in specialist burns services is highly challenging, and it may not always be possible to identify and eradicate the reservoirs of infection for P. aeruginosa outbreaks. Our study supports the literature, providing additional evidence that inanimate, common contact surfaces play an important role in nosocomial transmission of P. aeruginosa . These surfaces should either be decontaminated efficiently between patient contacts or be single patient use. Enhanced vigilance is crucial, and, with strict adherence to infection prevention and control procedures, it is possible to reduce the risk of acquisition and spread of infection in patients.